Psalm of praise for the rescue of the throat: concatenation and lectio continua of Pss 33–34–35 - Rodrigues, Edwin (Österreichische biblische Studien, 2022)
«Psalmenexegese und Psalterexegese» has become the new trend in the exegesis of the psalms. In its broad scope, this trend includes a method of combining a detailed exegesis of the selected individual psalms with the research to discover the rationale for their particular placement in the book of the Psalter. Following this method and doing the synchronic analysis, this research work first carries out the in-depth exegesis of Pss 33, 34, and 35. Then it applies the principles of concatenation and lectio continua to the results derived from the exegesis. This study establishes that there are sufficient thematic, structural, and lexical connections between these psalms to call them a «Psalm-Triad». This triad narrates a lucid story of תהלה in the context of the first book of the Psalter